Human 2009 influenza A (H1N1) virus infection in a premature infant born to an H1N1-infected mother: placental transmission? - Çetinkaya, Merih; Özkan, Hilal; Çelebi, Solmaz; Köksal, Nilgün; Hacımustafaoğlu, Mustafa (The Turkish Journal of Pediatrics, 2011)
Human infection with H1N1 virus reached pandemic status by the spring of 2009. Consequently, the rates of morbidity and mortality related with H1N1 2009 infections have been reported to be higher in pregnant women. H1N1 viremia is rare in the mother, and the risk for transmission of H1N1 2009 influenza from mother to fetus is unknown. To our knowledge, the literature contains only one previous report of a premature infant with H1N1 2009 infection whose mother also had H1N1 2009 infection. Here, we report an H1N1 pandemic influenza 2009-positive female premature infant born at 32 weeks of gestation whose mother had a confirmed H1N1 2009 infection by real-time reverse transcriptase polymerase chain reaction (rRT-PCR). This case suggests that H1N1 2009 virus might be transmitted across the placenta, and therefore, all infants born to an H1N1 2009-positive mother must be evaluated for possible H1N1 2009 infection.